Investigation on the water absorbency, chemical and thermal properties of superabsorbent poly (acrylic acid-co-acrylamide)/spent coffee ground composite - Lim, H. L.; S. N. A., Mazlan; Suriati, Ghazali; Syarifah, Abd Rahim; S. S., Jamari (IOP Publishing, 2020)
Superabsorbent polymer (SAP) is defined as a material that can absorb huge amount of water while remain its original shape without loss the water or aqueous solution that had been absorb. The incorporation of filler in SAP could increase the water absorbency of the polymer. Thus, this work aim to investigate the properties of spent coffee ground (SCG) biofiller into the SAP network using inverse suspension polymerization method. The structural, thermal and also morphological characterizations of the synthesized SAPs were performed by FTIR, TGA, and FESEM techniques. Based on the results obtained, the optimum of water absorbency of SAP was shown at SAP_0.05SCG filler respectively. For the effect of filler loading, the observed result was supported by FESEM microstructures of SAP where the surface morphology of all sample with varied filler composition shown coarse surface. It is observed using FTIR spectra that the O-H band is broader and sharper at SAP_0.05SCG compared to the control and the SCG filler. For the TGA, the SAP_0.05SCG is easier to thermally degrade compared to the control. Thus, this research has proved that the SCG is able to enhance the water absorbency of superabsorbent polymer which could give better contributions in various applications.